KANTIN KEJUJURAN BERBASIS TEKNOLOGI INFORMASI - Andayati, Dina (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Honesty cafeteria is now widely applied in schools, in order to educate students to learn about honesty. Honesty cafeteria formed upon the cooperation of Corruption Eradication Commission (KPK) and the AGO, in the framework of education as early as possible to students to be honest, to anticipate the act of corruption. Honesty cafeteria is a canteen that sells snacks and drinks. Unguarded honesty cafeteria, canteen available at the cash box, which is useful to accommodate the payment and when there is change, students take for change from inside the box. Honesty cafeteria-based information technology is one solution to minimize the dishonesty that occurs, because with honesty cafeteria system manually then there is still a lot of dishonesty. In honesty cafeteria manually box containing the money, opened freely by the students. While the use of information technology-based honesty cafeteria, the box containing the money could be locked because they do not need a refund.